Examining the impact of upright and recumbent positions on labor outcomes in Saudi Arabia: A quasi-experiment - Zahra Al Aryani; Abeer Orabi; Howieda Fouly (Belitung Nursing Journal, 2022)
Background: Helping the woman to adopt a comfortable position during childbirth significantly affects labor changes and pain management. However, there is a lack of consensus on the impacts of different childbirth positions on labor outcomes. In addition, a scarce of studies have assessed the effects of the upright and recumbent positions on delivery outcomes, especially in the Kingdom of Saudi Arabia. Objective: This study aimed to examine and compare the influence of upright and recumbent childbirth positions on birth outcomes. Methods: The setting was the childbirth unit at East Jeddah Hospital from November 2020 to March 2021. The research design was quasi-experimental, including 300 women in labor under 18-45 years. The sample includes two equal groups of 150 women: upright (experiment) and recumbent (comparison) position groups. Three tools were used to collect data: a structured interviewing questionnaire, the modified WHO partograph, and the Wong-Baker FACES® pain rating scale. Descriptive statistics, chi-square, independent t-test, and paired t-test were used for data analysis. Results: Women in the recumbent position spent a longer duration in the first, second, and third stages of childbirth and had higher pain scores and less satisfaction with the assumed position than women in the upright position, with a highly significant difference (p <0.001). Conclusion: Laboring women in upright positions experienced faster progress of labor, shorter duration of childbirth, less pain, and higher satisfaction than those assumed recumbent positions. This study serves as an input for midwives and nurses to enable them to offer appropriate advice to improve intrapartum care. In addition, educational programs targeting pregnant women about the positive impacts of upright position on women’s birth experience are encouraged.